(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This study aims to know about potential and attractions the jungle camp and the developments strategy by the jungle camp manageron jungle camp. There are two kinds of data sources in this research, namely primary data and secondary data. The researcher used direct observation and asked some question which have prepared by researcher. This study used a qualitative approaches. Data were collected from observation and interviewed in Bontoparang Gowa. There were two the Jungle Camp Manager and two Visitors of Jungle Camp as informans of this research. The result of this research showed that the development strategy carry out is for jungle camp tourism are the lack of management of the jungle camp so that this tour has not been convey to the Gowa government. And innovations that exist only from the creativity of local youth organizations.